Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2106/jbjs.cc.21.00136
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Femoral Shaft Fractures in Patients with Klippel-Trénaunay Syndrome

Abstract: Cases: Long-bone fractures in patients with Klippel-Trénaunay syndrome (KTS), a rare disorder of the venous, lymphatic, and capillary system, are difficult to treat with many complications. Two patients diagnosed with KTS presented with closed femoral shaft fractures after low-energy falls. Conservative treatment, open reduction internal fixation, and intramedullary nailing resulted in painful nonunions. Ultimately, both patients achieved pain relief and the ability to ambulate after en bloc resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There are only a few cases involving treatment of a femoral shaft fracture in KTWS and KTS patients and poor results were reported in these cases. Mahjoub et al 4) reported that conservative treatment such as skeletal traction and operative treatment such as open reduction and internal fixation (ORIF) or IM nail showed poor results in two cases of femoral shaft fracture in KTS patients. They eventually performed en bloc resection and reconstruction and insisted that it is a viable option 4) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are only a few cases involving treatment of a femoral shaft fracture in KTWS and KTS patients and poor results were reported in these cases. Mahjoub et al 4) reported that conservative treatment such as skeletal traction and operative treatment such as open reduction and internal fixation (ORIF) or IM nail showed poor results in two cases of femoral shaft fracture in KTS patients. They eventually performed en bloc resection and reconstruction and insisted that it is a viable option 4) .…”
Section: Discussionmentioning
confidence: 99%
“…Mahjoub et al 4) reported that conservative treatment such as skeletal traction and operative treatment such as open reduction and internal fixation (ORIF) or IM nail showed poor results in two cases of femoral shaft fracture in KTS patients. They eventually performed en bloc resection and reconstruction and insisted that it is a viable option 4) . Nahas et al 5) reported that ORIF for treatment of femoral shaft fracture in KTS patients resulted in delayed union, and management with low intensity pulsed ultrasound was subsequently administered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations